Understanding affordances in XR interactions through a design space - Vieira, Victor; Oliveira, Eder; Menin, Aline; Clua, Esteban; Winckler, Marco; Trevisan, Daniela (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
This paper presents a qualitative analysis of a literature review on affordances in XR environments. Affordances refer to the way how the system communicates to the user how to perform a task. Preliminary studies showed that there was no consensus and neither a standard taxonomy for describing affordances in XR. The goal of this study was to investigate how affordances were used as a strategy to promote discovery and usage in XR environments. We collected and analyzed works that describe affordance concepts and carry out experiments in 3D environments describing the applied affordances. We mapped the affordances usage in 8 dimensions: kind of environment, modality, location, temporal aspect, learning aspect, category of tasks, domain tasks and kind of affordance. Additionally, findings were categorized according to VR tasks and Bloom’s learning existing taxonomies. Finally, the relationship between the dimensions was analyzed and discussed as a tentative reflection and guidance on the future design and development of affordance taxonomy for XR environments.